Valproate-Induced Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Two adults, aged 32 and 37, with focal epilepsy developed hyperammonemic encephalopathy when treated with a combination of valproate (VPA) and topiramate (TPM) at the University of Marburg, Germany.